2003
DOI: 10.1109/tasc.2003.812392
|View full text |Cite
|
Sign up to set email alerts
|

Strain effects in high temperature superconductors investigated with magneto-optical imaging

Abstract: Abstract-In order to determine the influence of intermediate deformation steps on the mechanical behavior of Bi-based tapes, the effect of longitudinal applied strain is investigated by means of magneto-optical imaging. The strain is applied in a helium flow-cryostat. Cracks appear soon after the critical current in Bi-based tapes is degraded. All filaments form multiple cracks that grow into tape-wide cracks, running from one filament to the next. The crack location is not caused by stress concentrations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 13 publications
(12 reference statements)
3
25
0
Order By: Relevance
“…8 The sample was zero-field cooled to 30± 1 K on the cold finger of a helium flow cryostat. An external magnetic field of 25 mT ͑2% accuracy͒ was applied perpendicular to the surface of the tape to visualize the spatial variation in critical current density of the filaments.…”
mentioning
confidence: 99%
“…8 The sample was zero-field cooled to 30± 1 K on the cold finger of a helium flow cryostat. An external magnetic field of 25 mT ͑2% accuracy͒ was applied perpendicular to the surface of the tape to visualize the spatial variation in critical current density of the filaments.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Under no applied strain, the critical current is different from specimen to specimen and from position to position within a specimen. [18][19][20][21][22][23][24] Under applied strain, the damage evolution behavior is also different from specimen to specimen and from position to position within a specimen, resulting in wider distribution of critical current.…”
Section: Distribution Of Normalized Critical Current Of Bent Multifilmentioning
confidence: 99%
“…It has been shown that transport current in high-quality Bi-2223 tapes flows in part along pathways where grain boundaries form no significant barrier and where dissipation occurs within the grains. [20][21][22][23] The grains that make up this strongly linked backbone are connected at angles smaller than about 4°. Apart from this backbone, a number of other current paths also contribute to the overall critical current of the tape.…”
Section: A Parallel Path Modelmentioning
confidence: 99%